The need and convenience of harmonizing cross-border takeover regulation in the Pacific Alliance; Lessons from the U.S., U.K. and E.U. experience - Sanin Gómez, Juan Esteban (Revista de la Facultad de Derecho de México, 2020)
This article will answer the question of whether or not it is necessary and/or convenient to harmonize cross-border takeover regulation in the context of a Latin American economic block such as the Pacific Alliance. To this effect an overview of what the Pacific Alliance is, and the way how multiple economic sectors and areas have been integrated during the recent years will be made, specifically focusing on the creation and legal framework of the Latin American Integrated Market. Also, a general overview of the current takeover regulations of the four member countries will be analyzed in order to see where supranational regulation and harmonization is further needed in order to enhance and deepen the integrated market and the economic block as such. An analysis of the main lessons rendered throughout recent history from takeover regulation systems such as the U.S., U.K. and E.U. will allow us to make closing remarks[1]. [1]This research was made by the author after having taken the “Takeover Regulation” course taught by Dr. David Kershaw at the London School of Economics Executive LLM Program.